Desain Media Pembelajaran Fisika Berbasis Web Blog Pada Materi Translasi Dan Rotasi Kelas X SMK Bunda Auni Bekasi - Fregane Rematha; Sudirman Sudirman; Dandan Luhur Saraswati (UNIVERSITAS INDRAPRASTA PGRI, 2020)
The purpose of this study is to: (1) determine the design of web blog-based learning media in Physics lessons that can improve the understanding of class X students on the material of translation and rotation at SMK Bunda Auni Bekasi. (2) know the process of making physics learning media based on web blog. (3) knowing student responses after using physics learning media based on web blog. The method used in this research is descriptive qualitative which is carried out at SMK Bunda Auni Bekasi. The data collection technique used a questionnaire distributed to 29 students of class X Vocational High School. The research data was used to determine the design process of learning media based on web blogs and the responses of class X students to the products that have been made. The results of this research show that the students' responses to the design of physics learning media based on web blogs are based on a questionnaire assessment of 29 students, namely with a percentage of 79.7% of the ideal score and classified as